Project Management in Higher Education: Analysisof Best Practices Based on an Experience at a University in Costa Rica - Vargas Jiménez, Valeria (2025)
The article analyzes aspects susceptible to improvement in project managementat the vice-deanship Centro de Investigación y Docencia (CIDE)of the Universidad Nacional, Costa Rica. Through a qualitative studyinvolving interviews and document review, limitations were identified infive key organizational capacities: governance, processes, organizationalculture, human resources, and technology. The findings revealed the absenceof performance metrics, standardized procedures, leadership, andintegrated technological platforms, which hinders efficient managementaligned with institutional objectives. As a solution, it is proposed to implementproject management best practices based on international standardssuch as PMBOK and agile methodologies. These include strengtheningprocesses, professionalizing staff, establishing clear regulations, andmodernizing technology. The study concludes that effective project managementrequires the strategic integration of these capacities, supported by committed leadership, clear institutional policies, and an organizationalculture oriented toward continuous improvement and sustainability.